“Corporate Social Responsibility” (CSR) Antara Publisitas, Citra, dan Etika dalam Profesi Public Relations - Ani Yuningsih (MediaTor (Jurnal Komunikasi), 2005)
The field of PR activities are commonly focused on efforts to build strong brand image, product positioning, advertising, promotion and publicity. In the world of high competition, this strategy is not enough. Many multinational corporate nowadays choose Corporate Social Responsibility (CSR) as new strategy to build positive image and gaining good reputation. The existence of CSR program indicate corporate sense of social responsibility toward public interests. In practice, a tension between corporate need to build image and its consistencies toward moral integrity and social commitment was often found. Corporate often use its CSR program as a momentum of publicity instead of showing a real and genuine interest in community development. Therefore, an understanding to PR values and ethics was needed to plan and implement CSR program.